SISTEM IRIGASI BIG GUN SPRINKLER PORTABLE PERIODIK DENGAN MIKROKONTROLER ARDUINO - Muhammad Bilal Sulaiman Bahari; Albert Gunadhi; Andrew Joewono (Jurnal Elektro, 2020)
Barren land can have a social impact on people living in the surrounding area. Land that shouldbe used as dry land is caused by the condition of the land lacking water, so technology is needed thatcan improve the efficiency and effectiveness of water use, namely sprinkler irrigation. This sprinklerirrigation is supported by a big gun sprinkler that is capable of spraying water into the air as far as 20-30 meters, the water distributed can be uniform as rain so that production can be uniform and optimal.This method can take place if the sprinkler big gun that presses 2 to 6 bars is supplied with a waterpump that can provide that much pressure too. This system consists of a DHT22 sensor as an input toread the temperature and humidity values of the air. Arduino microcontroller as input processing fromtemperature and humidity sensors (DHT22) as well as main processing. The output is a water pumpand sprinkler that is used to spray water into the air. There are 3 main modes, namely auto, timer,manual, auto to run the tool automatically and periodically. Timer to run the system with time mode inminutes with a 10 minute increment in stages, manually to run the tool manually which needs to turnon and turn off the pump with the help of human power. The temperature changes carried out by thetool are the fastest with a duration of 3 minutes 42 seconds when the temperature of 33 degrees dropsto 32 degrees Celsius and the longest with a duration of 5 minutes 45 seconds. The most rapid changein humidity is 1 minute 35 seconds when 51 percent humidity rises to 52 percent and the longest with aduration of 3 minutes 1 second when 49 percent humidity rises to 50 percent. In testing the entire toolby running the auto mode the system will automatically turn on when the temperature <value is setand humidity> value is set and will automatically turn off.